Intramuscular Vaccination With the HSV-1(VC2) Live-Attenuated Vaccine Strain Confers Protection Against Viral Ocular Immunopathogenesis Associated With γδT Cell Intracorneal Infiltration - Nabi, Rafiq; Lewin, Andrew C.; Collantes, Therese M.; Chouljenko, Vladimir N.; Kousoulas, Konstantin G. (Frontiers in Immunology, 2021)
Herpes simplex virus type-1(HSV-1) ocular infection is one of the leading causes of infectious blindness in developed countries. The resultant herpetic keratitis (HK) is caused by an exacerbated reaction of the adaptive immune response that persists beyond virus clearance causing substantial damage to the cornea. Intramuscular immunization of mice with the HSV-1(VC2) live-attenuated vaccine strain has been shown to protect mice against lethal ocular challenge. Herein, we show that following ocular challenge, VC2 vaccinated animals control ocular immunopathogenesis in the absence of neutralizing antibodies on ocular surfaces. Ocular protection is associated with enhanced intracorneal infiltration of γδ T cells compared to mock-vaccinated animals and animals vaccinated with inactivated HSV-1(VC2) virus. The observed γδ T cellular infiltration was inversely proportional to the infiltration of neutrophils, the latter associated with exacerbated tissue damage. Inhibition of T cell migration into ocular tissues by the S1P receptors agonist FTY720 produced significant ocular disease in vaccinated mice and marked increased in neutrophil infiltration. These results indicate that ocular challenge of mice immunized with the VC2 vaccine induce a unique ocular mucosal response that leads into the infiltration of extracorporeal γδ T cells resulting in the amelioration of infection-associated immunopathogenesis.